2019
DOI: 10.1186/s40425-019-0652-7
|View full text |Cite|
|
Sign up to set email alerts
|

IL-27 enhances IL-15/IL-18-mediated activation of human natural killer cells

Abstract: Background Natural killer (NK) cells are an emerging new tool for cancer immunotherapy. To develop NK cell therapeutics from peripheral blood mononuclear cells (PBMCs) of healthy donors, substantial expansion of primary NK cells is necessary because of the very low number of these cells in peripheral blood. In this study, we aimed to investigate the effect of various cytokine alone or combinations, in expanded NK cells and to analyze the synergetic effect of cytokine combinations. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 47 publications
5
53
0
Order By: Relevance
“…In addition, use of IL-27 may enhance cytokine-mediated toxicity of NK cells. For example, the use of IL-15 can enhance NK cell cytotoxic function against ovarian cancer (167, 168) and IL-27 has been shown to enhance IL-15 mediated NK cell activation (169). This suggests that IL-27 should be further explored for use in combination with other cytokines to improve cytotoxic immune cell therapies.…”
Section: Il-27 Il-30 and Il-35: Influencing Cancer Developmentmentioning
confidence: 99%
“…In addition, use of IL-27 may enhance cytokine-mediated toxicity of NK cells. For example, the use of IL-15 can enhance NK cell cytotoxic function against ovarian cancer (167, 168) and IL-27 has been shown to enhance IL-15 mediated NK cell activation (169). This suggests that IL-27 should be further explored for use in combination with other cytokines to improve cytotoxic immune cell therapies.…”
Section: Il-27 Il-30 and Il-35: Influencing Cancer Developmentmentioning
confidence: 99%
“…For example, signaling through WSX-1 and gp130 on CD8 + T cells activated STAT1 and STAT4 and resulted in the increased expression of granzyme, perforin and IFN-γ in a T-bet-dependent manner [ 128 , 129 ]. In NK cells, the activation of STAT1/STAT4 by IL-27 stimulated T-bet-dependent IFN-γ production and IL-27R expression [ 130 , 131 ]. These overall pro-inflammatory effects of IL-27 can stimulate anti-tumor immunity and contribute to tumor cell clearance [ 130 , 131 , 132 ].…”
Section: Introduction Il-12 Family Cytokines: Composition Signalmentioning
confidence: 99%
“…Additional studies have demonstrated that NK cells mediate protective responses to MTB through their interactions with CD8 + T cells ( 66 ) and γδ T cells ( 67 ), and by directly engaging with infected macrophages ( 68 , 69 ). NK cell effector functions are associated with IL15, IL18, IL27 ( 70 , 71 ), and, specifically in the context of MTB infection, with IL21 ( 65 ), IL12 ( 72 ), TNFA ( 72 , 73 ) and IL22 ( 70 ). Vaccine-induced cytokine responses in the CPP of Silirum vaccinates reflected similar cytokine responses ( IL12 , IL21 , IL27 and TNFA ) that have previously been associated with NK cell activity.…”
Section: Discussionmentioning
confidence: 99%